Uso de portafolios electrónicos y rúbricas para desarrollar habilidades metacognitivas en el curso de historia del Perú en una institución educativa bilingüe de Lima - Alcázar Fernández, Jimena Lucía (2019)
Metacognitive skills are fundamental for self-directed learning and lifelong learning. If assessment is understood as intimately linked to learning, metacognitive skills must be placed at the centre of the process in order to encourage self-regulation of learning by assessing the own performance in order to deepen knowledge of achievements and needs and thus set concrete learning goals. The innovation that we present proposes to develop electronic portfolios of evaluation that incorporate holistic rubrics with the purpose of promoting the development of these skills in high school students. For this, it is important that teachers, before bringing innovations to the classroom, think about the meaning of assessment in schools and go through the process of developing portfolios and reflecting on their own learning.